Remote parenting in families experiencing, or at risk of, homelessness: a study based on grounded theory - Andrade, Filipa Maria Reinhardt (2024)
The situation/risk of family homelessness presents multiple interrelated issues. It has considerable negative consequences, namely the deterioration of the family members’ health and well-being, and alterations in the family’s dynamics, with parents sometimes being separated from their children. The aim of this research was to understand how parenting takes place in families experiencing, or at risk of, homelessness. The conducted study falls within the qualitative paradigm, using Strauss and Corbin’s version of the Grounded Theory methodology. Three main categories emerged, supported by all the participating families: “Meaning of Parenthood”, “Key Events”, and “Transition Circumstances”. These categories were translated into facilitating/inhibiting factors, within the following dimensions: “Individual”, “Family”, and “Society”. We were able to conclude that, in the population under study, parenting is restricted, being mostly exerted in a remote manner. Furthermore, it takes on different forms, depending on the specific homelessness situation/risk. In families at risk of homelessness, we identified “Remote Parenting with Maintained Parental Authority”, as well as “Restricted Parenting”, when the children still lived with their parents. On the other hand, in families experiencing homelessness, we identified “Remote Parenting with Maintained Parental Authority”, “Unilateral Remote Parenting”, “Interrupted Parenting”, and the “Total Disruption of Parenting”.